2021
DOI: 10.3390/cells10112940
|View full text |Cite
|
Sign up to set email alerts
|

Facing CAR T Cell Challenges on the Deadliest Paediatric Brain Tumours

Abstract: Central nervous system (CNS) tumours comprise 25% of the paediatric cancer diagnoses and are the leading cause of cancer-related death in children. Current treatments for paediatric CNS tumours are far from optimal and fail for those that relapsed or are refractory to treatment. Besides, long-term sequelae in the developing brain make it mandatory to find new innovative approaches. Chimeric antigen receptor T cell (CAR T) therapy has increased survival in patients with B-cell malignancies, but the intrinsic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 224 publications
(344 reference statements)
0
3
0
Order By: Relevance
“…The CAR T-cells on the other hand can also induce changes in the TME. For example, an increased production of INFg caused by the CAR T's, can induce immunostimulatory effects and inhibit the macrophages to differentiate to a M2-phenotype (78).…”
Section: Car T-cell Therapymentioning
confidence: 99%
“…The CAR T-cells on the other hand can also induce changes in the TME. For example, an increased production of INFg caused by the CAR T's, can induce immunostimulatory effects and inhibit the macrophages to differentiate to a M2-phenotype (78).…”
Section: Car T-cell Therapymentioning
confidence: 99%
“…The advances in the development of multi-antigen targeting CAR-T and the generation of CSC-specific CAR-T have enhanced confidence in its potential benefits in treating children with CNS tumours [ 175 , 176 , 177 ]. However, with no reports from large-scale trials and methodological challenges, such as the presence of the blood-brain barrier, the cross-expression of CSC markers in immature normal tissue, immune suppression by tumour microenvironment [ 178 , 179 ], treatment with CAR-T in targeting CSCs in paediatric CNS tumours still has a long way to go. The oncolytic virus was another potential way to target CSCs in children with CNS tumours, as an early review revealed multiple types of oncolytic viruses having the ability to kill CSCs [ 180 ].…”
Section: Clinical Significance Of Tumour Stem Cells In Tumours Of The...mentioning
confidence: 99%
“…The CAR‐T cell activity in the immunosuppressive TME can be inhibited by immune inhibitory ligands on the tumour cell surface, 122 which could induce T cell exhaustion, immunosuppressive cells, and immunosuppressive cytokines. 123 Major immunosuppressive cells include regulatory T cells (Treg), tumour‐associated macrophages (TAM) and myeloid‐derived suppressor cells (MDSC). Tregs secrete immunosuppressive cytokines which inhibit cytotoxic T cell function or limit the number of IL‐2 that can activate cytotoxic T cells.…”
Section: Overcoming the Immunosuppressive Microenvironmentmentioning
confidence: 99%
“…The immunosuppressive TME presents several challenges to CAR‐T cell therapy. The CAR‐T cell activity in the immunosuppressive TME can be inhibited by immune inhibitory ligands on the tumour cell surface, 122 which could induce T cell exhaustion, immunosuppressive cells, and immunosuppressive cytokines 123 . Major immunosuppressive cells include regulatory T cells (Treg), tumour‐associated macrophages (TAM) and myeloid‐derived suppressor cells (MDSC).…”
Section: Overcoming the Immunosuppressive Microenvironmentmentioning
confidence: 99%